Case of anti-Zic4 antibody-mediated cerebellar toxicity induced by dual checkpoint inhibition in head and neck squamous cell carcinoma. Issue 9 (17th September 2020) - Iyer, Sunil Girish; Khakoo, Nidah Shabbir; Aitcheson, Gabriella; Perez, Cesar
Abstract : Combined checkpoint inhibition therapy targeting the programmed cell death 1 (PD-L1) and cytotoxic T-lymphocyte associated protein 4 pathways has been a successful approach in the treatment of metastatic melanoma, leading to its investigation in the treatment of head and neck squamous cell carcinoma (HNSCC) with PD-L1 expression. Despite the potential for excellent responses, an increased rate of autoimmune neurological toxicity and paraneoplastic conditions has been observed when using these treatment modalities. We present the case of a patient with metastatic HNSCC treated with combination ipilimumab/nivolumab who experienced severe cerebellar ataxia with a positive screen for the anti-Zic4 antibody. This is the first case, to our knowledge, of anti-Zic4 antibody-mediated cerebellar toxicity reported in association with HNSCC. Although the patient experienced an impressive partial response with dual checkpoint inhibition, he suffered grade 4 neurotoxicity. Despite exciting advances in cancer immunotherapy, clinicians must be aware of the rare, debilitating and possibly previously undescribed paraneoplastic and autoimmune toxicities that may occur.